Competition Reform and Household Welfare : A Microsimulation Analysis of the Telecommunication Sector in Ethiopia - Rodriguez-Castelan, Carlos (World Bank, Washington, DC, 2021)
This paper presents a novel method for estimating the likely welfare effects of competition reforms for both current and new consumers. Using household budget survey data from 2015/16 for Ethiopia and assuming a reform scenario that dilutes the market share of the telecommunications state-owned monopoly to 45 percent, the model predicts a 25.3 percent reduction in the price of mobile services and an increase of 4.6 million new users of mobile phone services. This reform is expected to generate a welfare gain of 1.37 percent among all consumers. Poverty rates are expected to decline by 0.31 percentage point, driven by a reduction of 0.22 percentage point for current consumers and 0.09 percentage point among new users. Inequality would increase by 0.23 Gini point since better-off consumers are more likely to reap the benefits of greater competition. This method represents a powerful tool for supporting the analysis of competition reforms in developing countries, particularly in sectors known for excluding significant segments of the population due to high consumer prices.